Cancellation of work order for supply of remaining 3800 bags of OPC cement for BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding cancellation of work order for supply of remaining 3800 bags of OPC cement for BRAC University new campus project.